(untitled) (Journal of Scientific Research, 2017)
Mixed convection heat transfer in a two-dimensional the effect of hydromagnetic mixed convection in a double lid driven square cavity with inside elliptic heated block is studied numerically. The left wall of the square cavity and inside the elliptic block was kept at Th while the right wall of the square cavity at a cold temperature Tc with Th > Tc. The lid is assumed to be upper wall moving in left to right and lower wall right to left directions respectively. The magnetic field of strength B is applied parallel to x- axis. Result is presented firstly for different Reynolds number (50 ? Re ? 150), Prandtl number Pr= 0.733 and presented for different Grashof number (103 ? Gr ? 106). The numerical results studied the effect of Reynolds number, Grashof number and buoyancy ratio on the local values. It is found that direction of lid and different elliptic heated block are more effective on heat and mass transfer on fluid flow with increasing magnetic field for all studied parameters.